Ways of attracting of investments in public utilities of Ukraine - Чорній, Богдан Петрович (Technology audit and production reserves, 2013)
The article is devoted to problems of significant number of public utilities , forcing authorities to seek new mechanisms and approaches to the management of such enterprises. Partly such enterprises transformed into rynkovohospodaryuyuchyh subjects , and partly - become objects of purely social in providing public services. The aim of the research is to analyze the existing ways to attract private investment in municipal facilities and determine the most appropriate mechanisms for this economic area of Ukraine. The article describes the existing ways of attracting private investment in objects of communal property , analyzed the conditions of their administration. A comparative analysis of the use of public-private partnership model and procurement communal property social purpose. The advantages of public-private partnerships as compared with conventional scheme to attract private investment. The results of the comparison of the project through the mechanisms of public-private partnership with the traditional form of the investment projects can be concluded about the optimal use of PPP schemes , which leads to the most efficient financial management , quality of work and reduce the time of implementation, and the use of optimal design technology and building solutions to achieve a balance of high quality infrastructure and project costs.